Distinct association patterns of chemokine profile and cardiometabolic status in children and adolescents with type 1 diabetes and obesity - Špehar Uroić, Anita; Filipović, Maša; Šućur, Alan; Kelava, Tomislav; Kovačić, Nataša; Grčević, Danka (Frontiers in Endocrinology, 2024)
Objective: We compared peripheral blood (PBL) chemokine/receptor profiles in children and adolescents with type 1 diabetes mellitus (T1D) or obesity (OB) (both involving inflammation and vascular complications) to identify their associations with cardiometabolic risk factors.Materials and methods: PBL samples from children and adolescents (12-18 years) included: healthy controls (n=29), patients with T1D (n=31) and OB subjects (n=34). Frequency of mononuclear cell populations and chemokine receptor expression (CCR2, CCR4, CXCR3, CXCR4) were determined by flow cytometry. Chemokine levels of CCL2, CCL5, CXCL10 and CXCL11 were measured by beadbased assay and CXCL12 by ELISA. Data were correlated with cardiovascular, metabolic and inflammatory parameters.The proportion of CD14+ monocytes was higher in T1D, whereas CD19+ B lymphocytes was higher and CD3+ T lymphocytes was lower in obesity. The level of CCL2 was higher in T1D (241.0 (IQR189.6-295.3) pg/mL in T1D vs 191.5 (IQR158.0-254.7) pg/mL in control, p=0.033), CXCL11 was lower in OB (6.6 (IQR4.9-7.7) pg/mL in OB vs 8.2 (IQR6.9-11.3) pg/mL in control, p=0.018) and CXCL12 was lower in both diseases (2.0 (IQR1.8-2.5) in T1D, 2.1(IQR1.9-2.4) in OB vs 2.4 (IQR2.2-2.5) in control, p=0.016). Numerous significant associations were found for chemokine/receptor profiles and clinical data. Among these, we are pointing to the most important indicators of cardiometabolic risk in T1D: positive associations of CCR2 + monocytes with blood pressure and CCL12 levels with urine albumin-to-creatinine ratio (ACR), inverse association of CXCR3 + B lymphocytes with AST but positive with triglycerides; and OB: positive associations of CXCL12 levels with triglycerides and AST/ALT, inverse association of CCR4 + and CXCR3 + monocytes with ACR. Both diseases share positive associations for CCR4 + T lymphocytes and blood pressure, inverse associations of CXCR4 + subsets with ACR and CXCR3 + T lymphocytes with lipid profile.Significantly changed chemokine/receptor profiles were found in both T1D and OB even at a young age. Although different associations with cardiometabolic risk factors indicate diseasespecific changes, overlapping pattern was found for the associations between CCR4+ T lymphocytes and vascular inflammation, CXCR4+ subsets and albuminuria as well as CXCR3+ T lymphocytes and dyslipidemia. Thus, chemokine axes might present potential therapeutic targets for disease-related morbidity.